Modelling of blast and fragment loading effect - Mohamad Jauhari Johari (2017)
This thesis aims to study the influence of distance on the effects of blast loading towards the structural integrity of a building. Growing global apprehension about the malicious fangs of terrorism has forced the hands of many countries to anatomise their existing security measures. A compact city set-up, Singapore being a fitting example, is vulnerable towards terrorist attacks involving explosive devices. The availability of distance from a building to a potential threat source, known as stand-off distance, is perceived to one of the primary concerns when it comes to the issue of blast wave propagation. LS-DYNA is utilised to model and run various simulations of events, using reinforced concrete column as the representation of the structural integrity of a building. In addition, fragment loading, as well as combined blast and fragment loading, are briefly studied due to their relevancy. Upon observation, it is deduced that a large distance is a significant factor in suppressing the damaging effects of the aforementioned loadings. While only briefly studied, it is noted that combined blast and fragment loading is able to induce the most critical impact due to its combined nature. Therefore, a stricter implementation of stand-off distance is proposed.